Poultry value chains and HPAI in Indonesia: The case of Bogor - Sudarman, Asep; Rich, Karl M.; Randolph, Thomas; Unger, Fred (International Food Policy Research Institute, 2010)
Poultry is an important source of income and protein for poor households in Indonesia. In a normal year, the production of poultry meat in Indonesia is approximately 1.285 million tons per annum, representing around 62% of total domestic meat production. In addition, egg production amounts to 1.2 billion tons, with domestic production fulfilling domestic consumer demand for eggs. However, the entry of highly pathogenic avian influenza (HPAI) in Indonesia beginning in 2003 has had large negative impacts on rural livelihoods, both in terms of the production losses caused by the disease and the fears of its potential spread in humans. At present, HPAI is endemic throughout Indonesia and has affected all parts of the poultry business. Its spread in Jakarta, where a number of people died from HPAI, prompted the local government of Jakarta to adopt strict movement controls in controlling and monitoring poultry rearing and marketing in the metro Jakarta region.